(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable of God’s creation, Muhammad bin Abdullah, the faithful Messenger, his family, his companions, and those who follow him with goodness until the day God inherits the earth and whoever is on it, and he is the best of the inheritors.